Pengaruh Biaya Pendidikan Terhadap Mutu Sekolah SMA Swasta - Manoto Togatorop (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
This study aims to determine the direct influence of (1) participation in school quality, (2) the cost of education with school quality, (3) community participation with the costs of education. The method used is survey method with the correlational approach. In this study were used as a sample of 63 principals were selected based on random techniques (simple random sampling). Data were obtained by spreading questioner. This research was conducted in the district of Tangerang.Based on hypothesis testing that has been done, it can be described findings of the study as follows: (1) there is a direct positive effect between participation with school quality, (2) there is a positive direct influence between the cost of education with school quality, (3) there is a direct influence Among positive community participation with the costs of education.The implication of this research is the effort to improve school quality can be done through increased community participation and education expenses.